Collection of Arabic grammar for students of accelerated education (Journal of the College of Basic Education, 2022)
The current research aims to identify (the collection of Arabic grammar for students of accelerated education), the research sample was limited to students of accelerated education for the third level in the general directorates of education in the province of Baghdad for the academic year 2012/2013 AD, and their number is (3987) male and female students and they represent the total research community And the exploratory sample represented (300) from the total number of second Rusafa students, and the basic sample was (369) male and female students from the total sample of the original community, as they constitute a percentage of (10%). The researcher prepared an achievement test that verified its validity and reliability after presenting it to a group of students. Experts in the field of (Arabic language, teaching methods, measurement and evaluation).